2004
DOI: 10.1093/humrep/deh313
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of metaphase II human oocytes effects mitochondrial membrane potential: implications for developmental competence

Abstract: Irreversible loss of high DeltaPsim in thawed oocytes may be associated with defects in Ca2+ signalling after insemination and could have downstream consequences for normal embryogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
3
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(95 citation statements)
references
References 31 publications
5
85
3
2
Order By: Relevance
“…In MII mouse and human oocytes and embryos (Ahn et al 2002, 2003, Jones et al 2004, the highest intensity of J-aggregate fluorescence is reported to occur in the pericortical/subplasmalemmal cytoplasm (arrows, Fig. 1K).…”
Section: Is Mitochondrial Polarity (Dc M ) Related To Competence?mentioning
confidence: 97%
See 3 more Smart Citations
“…In MII mouse and human oocytes and embryos (Ahn et al 2002, 2003, Jones et al 2004, the highest intensity of J-aggregate fluorescence is reported to occur in the pericortical/subplasmalemmal cytoplasm (arrows, Fig. 1K).…”
Section: Is Mitochondrial Polarity (Dc M ) Related To Competence?mentioning
confidence: 97%
“…For example, owing to the absence of an intrafollicular vasculature, the oocyte may reside in a near anoxic The potential developmental relevance of pericortical J-aggregate fluorescence to high polarized mitochondria in the oocyte and early embryo, and differential J-aggregate fluorescence between the mural (mTR) and polar trophectoderm (pTR) and inner cell mass (ICM) are discussed in the text. Amy Jones provided image K (see also Jones et al 2004). Green fluorescence in this image is derived from JC-1 monomeric staining in low polarized mitochondria.…”
Section: Mitochondria As Metabolic Forces In Early Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Oocyte cryopreservation has been associated with intracellular organelles and cytoskeleton injuries, such as alteration in mitochondrial function [4], hardening [5] and fracturing [6] of the zona pellucida, microtubules damage [7,8], ultrastructural alterations in microdomains and meiotic spindle damage [9][10][11][12], which are presumably linked to the reduced developmental potential of cryopreserved oocytes [13]. However, protection of the meiotic spindle has been inferred by the addition of cryoprotectants [14] and by de novo spindle reconstruction following warming [15].…”
Section: Introductionmentioning
confidence: 99%